2019
DOI: 10.1029/2019gl082041
|View full text |Cite
|
Sign up to set email alerts
|

Intraslab Deformation in the 30 November 2018 Anchorage, Alaska, MW 7.1 Earthquake

Abstract: Anchorage, Alaska, was strongly shaken on 30 November 2018 by an MW 7.1 earthquake that ruptured within the underthrust Pacific plate at depths of from 45 to 65 km. Ground failures occurred in saturated lowlands filled with sediments, producing notable road damage, but there was limited structural damage in Anchorage, only ~12 km south of the epicenter. The earthquake has a normal faulting geometry with a shallowly dipping east‐west tension axis indicating intraslab deformation, likely between the underthrust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 25 publications
3
41
0
1
Order By: Relevance
“…C. Liu et al () suggested that the causative normal fault of the Anchorage earthquake is nearly N‐S oriented and dips westward with an angle of 65°. Southeast of this earthquake, focal mechanisms of most intraslab events during 2007 to 2008 in the Kenai Peninsula show also normal faulting, and their tensional axes are rotated dominantly in the E‐W direction rather than simply the slab dip direction (J. Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. Liu et al () suggested that the causative normal fault of the Anchorage earthquake is nearly N‐S oriented and dips westward with an angle of 65°. Southeast of this earthquake, focal mechanisms of most intraslab events during 2007 to 2008 in the Kenai Peninsula show also normal faulting, and their tensional axes are rotated dominantly in the E‐W direction rather than simply the slab dip direction (J. Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The USGS‐NEIC focal mechanism of the 2018 Anchorage earthquake shows that it was a normal‐faulting event occurring at 46.7‐km depth within the subducting Pacific slab (Figure ). The preferred fault model of C. Liu et al () shows that the causative fault strikes nearly N‐S and dips 65° westward. Previous focal mechanism studies (J. Li et al, ; Lu et al, ) revealed that intraslab earthquakes in this area are dominantly normal‐faulting type with an E‐W T‐axis and thus suggested that they are related to slab bending.…”
Section: Introductionmentioning
confidence: 99%
“…In the second step, we only invert the slip distribution by fixing the fault geometry derived from step one. Integrating both teleseismic and geodetic data, we solve the slip following a kinematic inversion finite‐fault strategy (Ji et al, ) with simulated annealing method (Sen & Stoffa, ), and we weight them equally (Liu et al, ).…”
Section: Source Modelmentioning
confidence: 99%
“…Integrating both teleseismic and geodetic data, we solve the slip following a kinematic inversion finitefault strategy (Ji et al, 2002) with simulated annealing method (Sen & Stoffa, 1991), and we weight them equally (Liu et al, 2019).…”
Section: 1029/2019ea000924mentioning
confidence: 99%
See 1 more Smart Citation